Sistem Pakar Diagnosa Penyakit DBD Pasien Puskesmas Tanjung Sarang Elang Menggunakan Metode Certainty Factor - Ainun, Annisa; Samsir, Samsir; Subagio, Selamat (LPPM Universitas Potensi Utama, 2025)
Health is valuable for humans, because anyone can experience health problems. Children are very susceptible to germs and lack of sensitivity to symptoms of a disease is a fear for parents. Parents are lay people who do not understand health. If a child has a health problem, they prefer to trust it to experts or specialist doctors who already know more about health, regardless of whether the problem is still at a low or chronic level. With the convenience of having experts or specialist doctors, sometimes there are also disadvantages such as limited working hours (practice) and many patients so they have to wait in line. In the rainy season, almost no area in Indonesia is free from dengue fever attacks. Research shows that dengue fever has been found in all provinces of Indonesia. Two hundred cities reported an Extraordinary Event (KLB). The incidence rate increased from 0.005 per 100,000 people in 1968 and drastically jumped to 627 per 100,000 people. An Expert System is a computer system designed to imitate the problem-solving abilities of an expert in a particular field using the knowledge and analysis methods that have been defined by the expert. The results obtained in using this system are the information system for DHF patients at the Tanjung Sarang Elang Health Center can be completed easily without requiring a lot of energy and time, does not require many files if more than one DHF disease data is needed and the data produced is free from errors. Thus it is expected to be very helpful in diagnosing DHF patients at the Tanjung Sarang Elang Health Center. Macromedia Dreamweaver is an HTML editor for designing, writing code (php) and as a program for processing and building websites, web pages and other web applications.